Comprehensive Molecular Profiling of Colorectal Cancer With Situs Inversus Totalis by Next-Generation Sequencing - Li, Hongsen; Gong, Liu; Cheng, Huanqing; Wang, Huina; Zhang, Xiaochen; Rao, Chuangzhou; Song, Zhangfa; Wang, Da; Lou, Haizhou; Lou, Feng; Cao, Shanbo; Pan, Hongming; et al. (Frontiers in Oncology, 2022)
Background Colorectal cancer (CRC) is one of the most prevalent malignances worldwide. However, CRC with situs inversus totalis (SCRC) is extremely rare, and molecular characterization of this disease has never been investigated. Methods Tumor tissue samples from 8 patients with SCRC and 33 CRC patients without situs inversus totalis (NSCRC) were subjected to multigene next-generation sequencing. Results The most frequently mutated genes in SCRC were APC, TP53, CHEK2, MDC1, GNAQ, KRAS, and SMAD4. A high frequency of SCRC tumors had mutations in DNA damage repair genes. Single amino acid substitutions in the DNA damage repair genes caused by continuous double base substitution was identified in the majority of this population. Furthermore, mutational profiles showed notable differences between the SCRC and NSCRC groups. In particular, CHEK2, MDC1, GNAQ, SMAD4, BRCA1, HLA-B, LATS2, and NLRC5 mutations were more frequently observed in SCRC patients. The mutation loci distributions of KRAS in the SCRC cohort differed from that of the NSCRC cohort. Additionally, differences in the targeted genomic profiles and base substitution patterns were observed between the two groups. Conclusions These findings comprehensively revealed a molecular characterization of SCRC, which will contribute to the development of personalized therapy and improved clinical management of SCRC patients.